Do we need to beware of students’ perceptions?: immediacy and emotional relationship between students and teachers in the Asian context - Lopez-Ozieblo , Renia (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Immediacy behaviour includes both verbal and non-verbal actions such as praising students, calling students by their names, using humour as well as using gestures, smiling, making eye contact or getting close to students. In a classroom context, immediacy affects the affective relationship between students and teachers as well as the content taught. From an intercultural perspective, Zhang (2006) and Lopez-Ozieblo (2015) have pointed out that some of the original items used to measure immediacy might not be relevant or appropriate in an Asian classroom, such as touching students or direct gaze. However, the bigger issue is, as Smythe and Hess (2005) noted, that most studies report retrospective students’ perception, after the class has finished, and not actual class observations. This study seeks to confirm previous findings reporting that perceived teachers’ behaviours could be correlated to learners’ evaluation scores of the class/topic and the teacher and to fill in that gap in the literature by correlating students’ perceptions with the reality observed in the classroom. The objective was to identify whether students’ perceptions of affective behaviours correspond to what happens in the classroom. Convenience sampling was used to gather naturally occurring data and was video recorded in eight hours of graduate (5 hours) and undergraduate (3 hours) lectures at the same Hong Kong institution. In addition, students were asked to fill in a teacher and class survey, evaluating how they perceived the teachers’ behaviours, whether they smiled, called them by their names, etc., during the session under observation. The results of our own observations and the students’ perceptions were correlated for the behaviours observed. Overall, our results confirm the findings of previous studies that correlate teacher immediacy behaviours with better students’ performance. Our results also suggest that students’ perceptions do usually reflect the reality of the classroom. Results also indicate moderate positive significant correlations between some of the actual behaviours and how learners evaluate the teacher. This suggests that, even in an Asian classroom, teachers should be aware of immediacy-developing behaviours.